(untitled) (European Journal of Marketing and Economics, 2018)
The main aim of this study is to investigate the impact of institutional obstacles and facilitators on innovative firms in Kosovo. In addition, we explore how the European and regional cooperation schemes help innovative entrepreneurs in Kosovo gain access to missing resources, financial capacities, and develop current institutional framework.